Cyclic Peptides with Antifungal Properties Derived from Bacteria, Fungi, Plants, and Synthetic Sources - Naiera M. Helmy; Keykavous Parang (MDPI AG, 2023)
Fungal infections remain a significant concern for human health. The emergence of microbial resistance, the improper use of antimicrobial drugs, and the need for fewer toxic antifungal treatments in immunocompromised patients have sparked substantial interest in antifungal research. Cyclic peptides, classified as antifungal peptides, have been in development as potential antifungal agents since 1948. In recent years, there has been growing attention from the scientific community to explore cyclic peptides as a promising strategy for combating antifungal infections caused by pathogenic fungi. The identification of antifungal cyclic peptides from various sources has been possible due to the widespread interest in peptide research in recent decades. It is increasingly important to evaluate narrow- to broad-spectrum antifungal activity and the mode of action of synthetic and natural cyclic peptides for both synthesized and extracted peptides. This short review aims to highlight some of the antifungal cyclic peptides isolated from bacteria, fungi, and plants. This brief review is not intended to present an exhaustive catalog of all known antifungal cyclic peptides but rather seeks to showcase selected cyclic peptides with antifungal properties that have been isolated from bacteria, fungi, plants, and synthetic sources. The addition of commercially available cyclic antifungal peptides serves to corroborate the notion that cyclic peptides can serve as a valuable source for the development of antifungal drugs. Additionally, this review discusses the potential future of utilizing combinations of antifungal peptides from different sources. The review underscores the need for the further exploration of the novel antifungal therapeutic applications of these abundant and diverse cyclic peptides.